How can we solve the puzzle of strategic climate management and appreciate its long-term effects? - Furlan Alves, Marcelo Berbone; Lopes de Sousa Jabbour, Ana Beatriz; Barberio Mariano, Enzo [UNESP] (Emerald, 2019)
Purpose: The purpose of this paper is to address the perceptions of managers in large companies located in Brazil regarding the long-term and short-term benefits of adopting strategic actions to mitigate and adapt to climate change. Design/methodology/approach: Based on an empirical analytical method, this paper examines interviews conducted with senior managers of leading companies located in Brazil to identify their perceptions of adopting strategic actions toward mitigating and adapting to climate change. Findings: The key results are as follows: the most commonly perceived long-term benefit was operational improvement, based on the improved energy efficiency of operations; strategic management of aspects affected by climate change can make managers more aware of the benefits derived from the decisions taken; and a short-term view and aversion to uncertainty can lead to failures in strategic management, limiting the effectiveness of actions for mitigating and adapting to climate change. Originality/value: This paper contributes to the literature on the topic of climate change by presenting evidence that adaptation and mitigation measures can increase organizational managers’ perception of long-term benefits, and that climate change management structures guide managers to make the transition to a low-carbon economy.
Keywords: Climate change; Organizational change; Sustainability; Sustainable development